(untitled) (Research, Society and Development, 2020)
Salted food bars are an alternative in order to reach sugar reduction consumption. The challenge to create this type of bar is to substitute sweet binding agents. This study intended to evaluate the technological and nutritional aspects of salted food bars elaborated with different concentrations of binding agents (modified starch, hydrolyzed collagen and acacia gum) with low caloric value. The basic ingredients (oats, linseed, soybean, sesame, quinoa, dehydrated tomato, seasonings such as garlic, onion and dehydrated parsley and NaCl) were added to the binding agent solutions. The food bars were analyzed chemically, physically and physicochemically. The results demonstrated that the three binding agents tested presented technical viability of agglutination of the ingredients. The food bars presented high content of dietary fiber, low caloric value, and high mineral (Fe, Zn, Mn and Mg) contents. Cereal bars produced with acacia gum presented higher texture values related to the chewability parameter, which had a positive influence.